2013
DOI: 10.1111/jocn.12177
|View full text |Cite
|
Sign up to set email alerts
|

Falling behind: a substantive theory of care for older people with cognitive impairment in acute settings

Abstract: The proposed substantive theory can be used to critically examine current ward practices and routines, and the extent to which these support or inhibit high-quality person-centred care for older patients with known or unknown cognitive impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
136
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(142 citation statements)
references
References 42 publications
4
136
2
Order By: Relevance
“…51,52 Cognitively impaired patients remaining on an acute psychiatric care unit present a major concern, mainly because these settings are often unable to adequately meet these patients' needs. 53,54 Finally, 8 patients in the nonacute group had a total hospital LOS of greater than 100 days, with 1 patient staying as long as 153 days. For the longest hospitalizations, a thorough chart review revealed 2 main reasons explaining the prolonged stays.…”
Section: 349mentioning
confidence: 99%
“…51,52 Cognitively impaired patients remaining on an acute psychiatric care unit present a major concern, mainly because these settings are often unable to adequately meet these patients' needs. 53,54 Finally, 8 patients in the nonacute group had a total hospital LOS of greater than 100 days, with 1 patient staying as long as 153 days. For the longest hospitalizations, a thorough chart review revealed 2 main reasons explaining the prolonged stays.…”
Section: 349mentioning
confidence: 99%
“…These include inflexible care routines that privilege the performance of medical and physical care tasks over time spent with patients, 27,28 and physical environments that are difficult to navigate. 21,22,25 The nature and quality of staff interactions with patients has been regarded as problematic, with staff encounters that are primarily task focused and involve limited engagement of the person at a personal level; [17][18][19]21,22,24,25,[29][30][31][32][33] and communication practices that are poorly responsive to the emotional needs of patients 17,[21][22][23][24][25]27,[30][31][32] and/or lead to a failure to 'see' and act on behavioural cues that might indicate distress or pain. 34,35 Studies have reported stigmatising and negative attitudes towards people with dementia among some staff and that such patients should not be admitted to acute wards.…”
Section: Care Of Hospitalised Older People With Dementiamentioning
confidence: 99%
“…34,35 Studies have reported stigmatising and negative attitudes towards people with dementia among some staff and that such patients should not be admitted to acute wards. 27,[29][30][31][32] Often conveyed as ensuring their safety and that of other patients, the consequence is to see people with dementia as 'other'. Conversely, staff with knowledge of dementia express lower perceived strain in caring for a person with dementia and less negative attitudes.…”
Section: Care Of Hospitalised Older People With Dementiamentioning
confidence: 99%
See 2 more Smart Citations